An exploration into early childhood physical literacy programs: A systematic literature review. Issue 1 (March 2023) - Porter, Joanne E.; Dabkowski, Elissa; Prokopiv, Val; Missen, Karen; Barbagallo, Michael; James, Michelle
This review explored the impact of physical literacy programs designed to engage two- to five-year-old preschool children. The Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) was used. Six EBSCO host databases were searched for the period 2011 to April 2021 using the search terms "physical literacy, " "early childhood, " and "impact." Articles were excluded if physical literacy was not the focal intervention. The final data set consisted of seven-peer reviewed articles meeting the eligibility criteria and quality assessment for this review. Three themes were created using Braun and Clark's (2006) approach to thematic analysis: Holistic benefits of physical literacy, Barriers to physical literacy and Education begins at home. Early childhood physical literacy programs provide holistic benefits for children; however, further research is needed in an Australian context. Families and community members working in the early childhood sector could benefit from further education and training to improve physical literacy awareness.